Honey Can Increase The Length of The Small Intestinal Villi in Malnourished Albino Rats - Listyorini, Linda; Mustofa, Imam; Hernawati, Tatik; Rimayanti, Rimayanti; Suprayogi, Tri Wahyu; Safitri, Erma - (Jurnal Medik Veteriner, 2021)
The aim of this study was to determine the potential of honey to the length of small intestine villi of albino rats due to nutritional deficiencies. The experimental animals were used 24 male albino rats with a body weight of 250-300 grams, divided into four groups and each group contained six replication. Negative control (K-) was a group of rat without fasting and without honey. Positive control (K +) was a group of rat with fasting conditions for 5 days and without honey. The treatment group was the rat with fasting conditions for 5 days and given honey therapy at a dose of 30% (P1) and 50% (P2). Data analysis used ANOVA (Analysis of Variants) then continued with the Duncan Multiple Range test with a significance level of 5% it can be seen that the length of small intestine villi was obtained at (K-) which is 531,321 ± 0,64 which is not significantly different (p>0,05) from (P2), which is 519,919 ± 0,49, but is significantly different (p<0,05) with other treatments (K+) 360,564 ± 0,87 and (P1) 434,275 ± 0,40. The conclusion of this study is that giving honey has the potential to increase the length of the intestinal villi of albino rats due nutritional deficiencies.